"Psychological" elements in business cycle theories: old approaches and new insights. Issue 3 (3rd May 2016) - Geiger, Niels
Abstract: This paper identifies a number of "psychological" elements in business cycle theories and shows how these components contribute to the theories' results. It proceeds by discussing (i) which assumptions on behaviour were used, laying particular stress on expectations and confidence, money illusion, social preferences and interaction, and individual character traits; (ii) how they influenced and determined the theories' results; and (iii) how more recent behavioural research provides a better and empirically grounded understanding of these factors. For each element, the possibility of incorporating new insights into older models is discussed, and references to work which already does so are given.